2009
DOI: 10.1111/j.1752-699x.2008.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic role of BAL fluid CD4/CD8 ratio in different radiographic and clinical forms of pulmonary sarcoidosis

Abstract: BAL is a valuable method in diagnostic pathway of pulmonary sarcoidosis. However, results of BALF examination must be interpreted considering a specific clinical case. BALF CD4/CD8 ratio depends on clinical and radiographic manifestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 37 publications
(49 reference statements)
2
32
0
4
Order By: Relevance
“…They also found that optimal cut-off points for CD4/CD8 ratio are 3.5 and 4.0 for asymptomatic and symptomatic patients, respectively. 66 In the present study, TBLB was performed in 36.6% of the patients (i.e. 11/30) and more than half of them were diagnostic (i.e.8/11).…”
Section: Resultsmentioning
confidence: 99%
“…They also found that optimal cut-off points for CD4/CD8 ratio are 3.5 and 4.0 for asymptomatic and symptomatic patients, respectively. 66 In the present study, TBLB was performed in 36.6% of the patients (i.e. 11/30) and more than half of them were diagnostic (i.e.8/11).…”
Section: Resultsmentioning
confidence: 99%
“…However, cellular components of BALF and T lymphocyte profiles are associated with several situations, such as clinical presentation, radiological stage and smoking status (17,18). A high relative CD4 + T lymphocyte number (percentage) and high CD4/CD8 ratio, increased alveolar macrophages amount in BALF reflect an active inflammatory process in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…BALF analysis was performed as described in previous publications (17,18). We used the same BAL and BALF methods of analysis throughout the study period.…”
Section: Bronchoscopy and Bronchoalveolar Lavagementioning
confidence: 99%
See 2 more Smart Citations